Synthesis of mesoporous layered iron oxide/rGO composites for stable sodium- and lithium-ion batteries - Peng, Junjun (2024)
Iron oxides, such as FeOOH, Fe2O3, and Fe3O4, are promising materials for sodium-ion (NIBs) and lithium-ion (LIBs) batteries. However, the preparation of stable iron oxides for NIBs and LIBs usually involves intricate routes. In this work, we develop simple approaches for the synthesis of stable mesoporous layered iron oxide (FeOOH, Fe2O3, or Fe3O4)/reduced graphene oxide (rGO) composites for NIBs and LIBs. The approaches first involve the synthesis of rod-like-FeOOH/graphene oxide (GO) sheets via hydrolysis and electrostatic attraction. Rod-like FeOOH flattens the GO, which facilitates layered-assembly. Two reduction-induced self-assembly methods, i.e., hydrazine-assisted reduction and heat treatment can then be employed to prepare layered FeOOH/rGO and layered Fe2O3/rGO, respectively, from the flat FeOOH/GO sheets. Further thermal treatment of the layered FeOOH/rGO enables the formation of Fe3O4/rGO. All these materials possess mesoporosity. The mesopores of the materials provide preserved void spaces for volume expansion during sodiation and lithiation. The layered rGO framework serves as a conductive medium for the transport of electrons. As a result, the layered materials exhibit stable cyclability for both sodium and lithium storage. Notably, the layered FeOOH/rGO composite exhibits an impressive ability to withstand ∼1000 cycles without experiencing significant capacity decay for sodium storage.